333 Associations Between Insomnia and Health Correlates in Nurses. (3rd May 2021) - Nagy, Samantha; Dietch, Jessica; Slavish, Danica; Messman, Brett; Ruggero, Camilo; Kelly, Kimberly; Taylor, Daniel
Abstract: Introduction: Insomnia, shiftwork (i.e., circadian rhythm disruptions) and insufficient sleep are common among nurses and healthcare workers. Each of these sleep problems can contribute to physical (e.g., inflammation, musculoskeletal pain, cardiovascular disease and heart rate variability, indigestion, and menstrual cycle irregularity) and mental (e.g., depression, anxiety, suicidality) health problems as well as daytime fatigue and sleepiness among nurses and may contribute to burnout and job change. Methods: Participants (N=458) were nurses recruited for a parent study, "Sleep and Vaccine Response in Nurses (SAV-RN)" (Taylor & Kelly: R01AI128359-01). Most identified as female (90.5%), White/Caucasian (77.2%), and non-Hispanic (88.6%) with an average age of 39.03 (SD = 11.07). Participants completed baseline measures online via Qualtrics survey. The Sleep Condition Indicator (SCI; Espie et al., 2014) was used to identify a probable diagnosis of insomnia (score of ≤16 = Insomnia; endorsement of each of the primary DSM-5 criteria on the measure). In addition, a checklist of current major health conditions (high blood pressure, sleep apnea, GI issues, HIV/AIDS, cancer, etc.) was also completed. A Chi square test of Independence was conducted using SPSS to determine if insomnia detected by the SCI was associated with reported health conditions. Results: At baseline, 25.4% of nurses had a probable insomnia diagnosis. Insomnia was associated with a greater likelihood of diagnosed sleep apnea, cancer (all types), high blood pressure, chronic pain, gastrointestinal problems, an autoimmune disease, and/or an endocrine problem at Month 11 of the study (all ps <.05). Data cleaning is ongoing, but similar analyses will be presented examining shift work sleep disorder and insufficient sleep (i.e., average < 6hrs per night) as individual and simultaneous predictors of physical and mental health at baseline and change from baseline to Month 11 (if available). Conclusion: These results help to identify associations between insomnia and health conditions in nurses and may contribute to future research that supports evidence-based intervention and prevention strategies for this population. While evidence-based interventions for sleep disturbances and insomnia exist (CBT-I), accessibility and feasibility of scaling such interventions to reach the nursing community at large remains challenging. Support (if any):